Figure 2 from: Sikes D, Stockbridge J (2013) Description of Caurinus tlagu, new species, from Prince of Wales Island, Alaska (Mecoptera, Boreidae, Caurininae). ZooKeys 316: 35-53. https://doi.org/10.3897/zookeys.316.5400 - Sikes, Derek; Stockbridge, Jill (Zenodo, 2013)
Figure 2 - Habitats of Caurinus tlagu A Habtiat of type locality, thinned secondary growth with 18 ft. spacing between trees, 55.88433, -132.89734 B example of old growth habitat in which specimen UAM:Ento:204239 was found, 55.88602,-132.8607 C example of clearcut, a habitat type in which seven specimens were found, 55.872, -133.06523 D example of treeless, alpine heath – tundra in which two specimens were found, 55.58818, -132.88881.